1998
DOI: 10.1093/nar/26.9.2208
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory studies on azole carboxamides as nucleobase analogs: thermal denaturation studies on oligodeoxyribonucleotide duplexes containing pyrrole-3-carboxamide

Abstract: In order to study base pairing properties of the amide group in DNA duplexes, a nucleoside analog, 1-(2'-deoxy-beta-D-ribofuranosyl)pyrrole-3-carboxamide, was synthesized by a new route from the ester, methyl 1-(2'-deoxy-3',5'-di-O-p -toluoyl-beta-D-erythro-pentofuranosyl)pyrrole-3-carboxylate, obtained from the coupling reaction between 1-chloro-2-deoxy-3,5-di-O -toluoyl-d-erythropentofuranose and methyl pyrrole-3-carboxylate by treatment with dimethylaluminum amide. 1-(2'-Deoxy-beta-D-ribofuranosyl)pyrrole-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 55 publications
2
35
3
Order By: Relevance
“…The parameters for the A@A:T and M@T:A triads are virtually identical if the 3-nitropyrrole occupies a position in which the hydrophobic C5 methyl is in van der Waals contact with the C4-H and NO 2 group of the nitropyrrole. Recent results indicated that 3-nitropyrrole greatly prefers to pair opposite itself rather than a hydrogen bonding base (51), and hydrogen bonding studies by NMR showed that 3-nitropyrrole exhibits virtually no hydrogen bonding association with the natural bases. As discussed in the Results section, models show that if A, C or G was placed opposite 3-nitropyrrole in the triad, there would have to be a significant shift in base position to achieve van der Waals contact.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters for the A@A:T and M@T:A triads are virtually identical if the 3-nitropyrrole occupies a position in which the hydrophobic C5 methyl is in van der Waals contact with the C4-H and NO 2 group of the nitropyrrole. Recent results indicated that 3-nitropyrrole greatly prefers to pair opposite itself rather than a hydrogen bonding base (51), and hydrogen bonding studies by NMR showed that 3-nitropyrrole exhibits virtually no hydrogen bonding association with the natural bases. As discussed in the Results section, models show that if A, C or G was placed opposite 3-nitropyrrole in the triad, there would have to be a significant shift in base position to achieve van der Waals contact.…”
Section: Discussionmentioning
confidence: 99%
“…1.4.25), which was originally designed as a universal nucleobase, pairs with almost equal affinity to each of the natural bases. However, a 12-mer duplex with nitropyrrole opposite itself is significantly more stable than the same duplex with nitropyrrole opposite each of the natural bases (Bergstrom et al, 1995;Zhang et al, 1998). The significance of the hydrophobic substituent (nitro) in mediating this effect is clear when one com-pares pyrrole-3-carboxamide, which in duplex DNA yields far more stable duplexes when paired opposite each of the natural bases than when paired opposite itself.…”
Section: Non-hydrogen-bonding Base Pairsmentioning
confidence: 99%
“…3-Nitropyrrole deoxyribonucleoside (S.26; Fig. 1.4.8), which was originally designed as a universal nucleobase, pairs with almost equal affinity to each of the natural bases, but a 12-mer duplex with nitropyrrole opposite itself is significantly more stable than the same duplex with nitropyrrole opposite each of the natural bases (Bergstrom et al, 1995;Zhang et al, 1998). The significance of the hydrophobic substituent (nitro) in mediating this effect is clear when one compares pyrrole-3-carboxamide, which in duplex DNA yields far more stable duplexes when paired opposite each of the natural bases than when paired opposite itself.…”
Section: Hydrophobic Base Pairsmentioning
confidence: 99%
“…Modeling studies with azole carboxamides paired with the four natural bases in a B‐DNA duplex show that two important parameters of base‐pair geometry are maintained: the C1′ to C1′ distances are in the range of 10.8 to 11.0 Å, and λ 1 and λ 2 are ∼50°. Models of azole carboxamide base pairs with a natural base pair yield C1′ to C1′ distances that fall within 0.2 Å and λ 1 and λ 2 within 3° of the natural base pairs (Bergstrom et al, ; Johnson et al, ; Zhang et al, ). 1,2,4‐Triazole‐3‐carboxamide deoxyribonucleoside illustrates the difficulty of predicting both structural and biochemical behavior of nucleoside analogs.…”
Section: Degenerate Basesmentioning
confidence: 99%